Инженерная графика электронный курс - Долотова Р. Г. Раиса Григорьевна; Винокурова Г. Ф. Галина Федоровна; Буркова С. П. Светлана Петровна; Антипина Н. А. Наталья Алексеевна (Томск, TPU Moodle, 2016)
Заглавие с экрана